Bibliometric indicators of endodontics in Cuban medical journals - Teresita de Jesús Clavera Vázquez; Alain Manuel Chaple Gil; Josefa Dolores Miranda Tarragó; Javier Álvarez Rodríguez (Editorial Ciencias Médicas, 2015)
Introduction: scientific communication materializes through the publication of papers in specialized journals. This is the reason why the quantitative study of journals, known as bibliometry, is a method allowing to evaluate scientific development. Objective: determine the characteristics of scientific production about endodontics in Cuban medical journals until the present moment. Methods: a cross-sectional observational descriptive study was conducted. The study universe was composed of 22 116 papers. The study sample was all the papers about endodontics (25 papers) published by Cuban authors in Cuban medical journals until the year 2014. All papers were included irrespective of the language in which they were written. The search was conducted in SciELO, the Virtual Health Library and the SCAD service. The search terms used were endodontics, root canal treatment, pulp therapy(ies) and combinations thereof. Results: of the 25 papers about endodontics, four had been published in the last five years. The number of authors per paper was three (32 %). Most authors (24 %) were from the School of Dentistry of Havana. 83.3 % of the sample were original papers. There was a predominance of papers about therapeutics (40 %). Conclusions: cuban scientific production on endodontics is scarce. The publication with the largest number of papers on the subject is the Cuban Journal of Dentistry. Therapies are the most common topic. The most productive institution is the School of Dentistry of Havana.